AN ANALYTICAL STUDY OF DECISION-MAKING CONTROL LEVELS AMONG TRACK AND FIELD COACHES FROM THE PLAYERS' PERSPECTIVE - Dr. Saif Hadi Mingal (Journal Park Publishing, 2024)
The importance of this research lies in obtaining a standardized measure to control decision-making, revealing the levels of decision-making skills possessed by the sample. This can contribute to making appropriate and accurate decisions during training and competition. Presenting the study's results to researchers and trainers can facilitate the application of these findings in sports, emphasizing the current research problem by shedding light on the nature of decision-making and its levels among track and field coaches. This aims to identify strengths in decision-making, enhance them, and address weaknesses based on rigorous scientific principles. These findings are intended to be accessible to coaches to assist them in making sound decisions built on a positive understanding of various situations. Given the significance of these variables, they need to be scientifically studied, and a crucial step in this regard is the development of an accurate scale. The research focuses on constructing a decision-making control scale for track and field coaches for the sports season 2022-2023. The research objectives include identifying the level of decision-making control among track and field coaches for the 2022-2023 season and determining the standard levels of decision-making control for track and field coaches during the same season. The researcher employed a descriptive survey methodology with a relational approach.
Keywords: Levels of Decision-Making Control